2020
DOI: 10.24996/ijs.2020.61.4.11
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Particles and Minerals Content in Soft Clay Soil of the Mekong Delta Coastal Provinces, Southern Vietnam for Inorganic Adhesives Stabilization

Abstract: The paper aims at investigating the content of particles and minerals of soft clay soil in the Mekong Delta coastal provinces, southern Vietnam, as well as improving soil stability using inorganic adhesives, i.e.lime and cement-based stabilization. To study the composition of soft clay soil, a series of different laboratory methods were carried out and revealed various characteristics related to mineral composition, pH value, soluble salt content, and grain particle composition of soft clay soils. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
3
1
1
Order By: Relevance
“…We observed an abundance of kaolinite in the soil matrix. This result was consistent with another study by Nu et al (2020) that found a higher amount of kaolinite, and illite in soft clay soil. This clay mineral would affect the swelling, plasticity, and compression properties of the soil.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…We observed an abundance of kaolinite in the soil matrix. This result was consistent with another study by Nu et al (2020) that found a higher amount of kaolinite, and illite in soft clay soil. This clay mineral would affect the swelling, plasticity, and compression properties of the soil.…”
Section: Discussionsupporting
confidence: 93%
“…The soft clay soil was distinguished by a silty clay texture (Table 1) with the percentage of clay content was around 44-48%. This result was consistent with a study by Nu et al (2020) who obtained total clay content in the soft clay samples of the Mekong Delta Region of Vietnam was ranged from 44 to 50%. In general, the parent material could contribute to a significant impact on the soil particle composition.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations